It’s OK Not To Be OK : Pengalaman Psikologis pada Perawat yang Menangani Pasien Covid-19 - Ika Febrian Kristiana (Universitas Muhammadiyah Jember, 2022)
The Covid-19 outbreak in Indonesia has had a psychological impact on nurses as the vanguard of handling Covid-19. Psychological hazards to nurses must receive attention because they affect the quality of health services provided. This study aims to describe the psychological experiences of nurses in dealing with Covid-19 patients. A phenomenological qualitative approach is used to describe the experience of nurses. Four participants who agreed to have been involved in this study and were interviewed in-depth online. Data analysis was carried out following procedures from psychological phenomenology (Moustakas, 1994). The results of the analysis show that there is a negative psychological response at the beginning of carrying out Covid-19 handling tasks, including anxiety, fear, and sadness to cause psychosomatic problem. Performing adaptive stress coping (Problem-focused) makes the psychological response of nurses more positive despite the fluctuations and contradictions of emotion-cognition in subsequent experiences, for example: tired vs proud, longing vs sad. Several things that determine the positive psychological experience of nurses include coping strategies; personal protective equipment, hospital facilities, welfare improvement, family support, and community compliance with health protocols. The social stigma that Covid-19 nurses can transmit the virus creates an attitude of rejection from the community. Thus, the results of this study can be considered in developing psychological interventions for nurses and psychosocial policies to educate the public.